Copy-number variation of housekeeping gene rpl13a in rat strains selected for nervous system excitability - Kalendar, Ruslan; Belyayev, Alexander; Zachepilo, Tatiana; Vaido, Alexander; Maidanyuk, Dmitry; Schulman, Alan H; Dyuzhikova, Natalia (Molecular and cellular probes, 2017)
We evaluated copy number variation (CNV) for four genes in rat strains differing in nervous system excitability. rpl13a copy number is significantly reduced in hippocampus and bone marrow in rats with a high excitability threshold and stress. The observed phenomenon may be associated with a role for rpl13a in lipid metabolism.
Keywords: hipokampus; variabilita počtu kopií segmentů DNA; kostní dřeň; Animals; kortikální excitabilita; DNA Copy Number Variations; ribozomální proteiny; Cortical Excitability; krysa rodu Rattus; zvířata; Bone Marrow; Ribosomal Proteins; Nervous System Physiological Phenomena; nervový systém - fyziologické jevy; Rats; Hippocampus